2020
DOI: 10.1002/ange.202005377
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Growth of a Spatially Localized Supramolecular Hydrogel with Autocatalytic Ability

Abstract: Autocatalysis and self‐assembly are key processes in developmental biology and are involved in the emergence of life. In the last decade both of these features were extensively investigated by chemists with the final goal to design synthetic living systems. Herein, we describe the autonomous growth of a self‐assembled soft material, that is, a supramolecular hydrogel, able to sustain its own formation through an autocatalytic mechanism that is not based on any template effect and emerges from a peptide (hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…[14] Hydrogels formed through enzyme-assisted self-assembly of peptides exhibited highly efficient esteraselike activity. [15] However, developing enzyme-driven dynamic catalytic switches remains challenging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Hydrogels formed through enzyme-assisted self-assembly of peptides exhibited highly efficient esteraselike activity. [15] However, developing enzyme-driven dynamic catalytic switches remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Enzyme‐driven dynamic self‐assembly has been widely used in tumor therapy and bioimaging [14] . Hydrogels formed through enzyme‐assisted self‐assembly of peptides exhibited highly efficient esterase‐like activity [15] . However, developing enzyme‐driven dynamic catalytic switches remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…This opened the route to the precise localization of peptide self-assemblies, and a step that was taken in 2009 when Williams and Ulijn groups showed that peptide self-assembly can be initiated from covalently immobilized enzyme on a surface [ 10 ]. Our group further developed the localized enzyme-assisted self-assembly (LEASA approach by introducing seed-layers in addition to an enzyme-adsorbed layer to trigger the localized self-assembly growth [ 11 , 12 ], for catalytic and auto-catalytic self-assembled hydrogels [ 13 , 14 , 15 ] or self-assemblies initiated from nanoparticles surface [ 16 ] and in host materials [ 17 , 18 ]. This bottom-up approach is efficient in water and once the surface coated with an adequate enzyme, the localized self-assembled structure growth proceeds in an autonomous way [ 19 ].…”
Section: Introductionmentioning
confidence: 99%